The Impact Of Lifestyle, Brand Awareness, Product Quality, On Purchasing Decisions And Repurchase Intention - Julianti Fernanda Pasaribu; Santirianingrum Soebandhi; Joko Suyono; Damarsari Ratnasahara Elisabeth (Journal of World Conference (JWC), 2020)
A large number of Indonesian people who live a healthy lifestyle makes organic agricultural products increasingly in demand because they have the best quality and health. Indonesia is a country that has a large population and is one of the countries that has an area of ??organic farming. Business people see the existence of organic food business opportunities to present products that are in line with market desires and stick to the hearts of consumers. Therefore, this study was prepared to analyze the impact of Lifestyle, Brand Awareness, and Product Quality on Purchasing Decisions and Repurchase Intention. This research is a quantitative research with a survey approach that uses a questionnaire of 100 respondents from consumers who buy organic products at the Surabaya Supermarket. The analysis technique used to prove the hypothesis is Partial Least Square (PLS). These results indicate that Lifestyle, Brand Awareness, Product Quality have a significant effect on Purchasing Decisions, and Purchasing Decisions have a significant effect on Repurchase Intention.